Maqashid Sharia in Millennial Da'wah - Mohammad Adnan; Badrah Uyuni (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
Islamic da'wah should be understood as an activity that involves a transformation process that does not just happen but requires awareness from the community to change the situation and condition of the people towards benefit through education and continuous communication. The study in this article uses a qualitative research model with library research techniques and focuses on the study of Islamic da'wah with a maqashid sharia approach. The question to be answered in this study is how da'wah can answer the needs of the people so that it can bring benefits. And as a conclusion, the importance of placing maqashid sharia in every Islamic da'wah. So that Islamic da'wah is not only understood textually but can also be understood contextually so that what is conveyed can be made sense by reason.Keywords: maqashid syariah, environment, fatwa, ushul fiqih AbstrakDakwah Islam semestinya dipahami sebagai suatu aktivitas yang melibatkan proses transformasi yang memang tidak terjadi begitu saja, tapi membutuhkan kesadaran dari masyarakat untuk merubah situasi dan kondisi umat menuju kemaslahatan melalui pendidikan dan komunikasi yang berkelanjutan. Kajian dalam artikel ini menggunakan model penelitian kualitatif dengan teknik library research dan terfokus pada kajian dakwah Islam dengan pendekatan maqashid syariah. Pertanyaan yang ingin dijawab dalam studi ini adalah bagaimana dakwah mampu menjawab kebutuhan umat sehingga bisa membawa kemaslahatan. Dan sebagai konklusi pentingnya menempatkan maqashid syariah dalam setiap dakwah keislaman. Sehingga dakwah Islam tidak hanya dipahami secara tekstual saja namun dapat juga dipahami secara kontekstual, sehingga apa yang disampaikan dapat dinalar oleh akal.Kata kunci: maqashid syariah, lingkungan hidup, fatwa, ushul fiqih